(untitled) - John Holton [et al.] (Cambridge, Massachusetts, 1995)
This book attempts to provide the student with practice in interpreting laboratory results within the context of a clinical microbiological problem. It covers the entire field of medical microbiology in three sections: bacteriology and mycology, virology, and parasitology
Keywords: bacterial infections - diagnosis - problems,medical microbiology - examinations, questions, etc,parasitology - problems,virus diseases - drug therapy - problems